Parallel folding pathway of proline-free staphylococcal nuclease studied by the stopped-flow double-jump method. Issue 2 (2003) - Kamagata Kamagata, Kiyoto Kiyoto; Kuwajima Kuwajima, Kunihiro Kunihiro
Abstract : The folding mechanism of proline‒free staphylococcal nuclease (SNase (pro − )) (P11A, P31A, P42A, P47T, P56A, P117G) was investigated using the double‒jump stopped‒flow method (interrupted refolding). This method has enabled us to specifically monitor the amount of the native molecules during the refolding. The results indicate that the middle and slow phases observed in the refolding kinetics represent the formation of the native state (IM →N, IS →N) and that the folding mechanism of SNase (pro − ) is not represented by a single sequential pathway, but at least two parallel pathways are required for interpreting the results.